Estimativa da frequência da inversão SWBinv-1 entre pais de portadores ds síndrome de Williams-Beuren e pais de filhos normais do Brasil - Loaiza Medina, Juan Diego [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Williams-Beuren syndrome (WBS) is a rare genetic disorder characterized by various physical abnormalities, including facial dimorphisms, cardiovascular abnormalities, intellectual disability and growth characteristic cognitive profile and occasionally transient infantile hypercalcemia, with a prevalence of 1/7500 . The etiology of SWB is a hemizygous deletion of contiguous genes at chromosome region 7q11.23. The most common sizes of deletions are 1.5 and 1.8 Mb and encompass 28 genes. The mechanism of deletion is directly linked to repetitive chromosomal regions, called Low Copy Repeats (LCR). These repetitive regions are distributed throughout the genome, constituting about 5% of its total and are the substrate for chromosomal recombination (crossing-over) during the meiotic process. In some instances the process of recombination can occur unevenly among homologous non-allelic (homologous recombination nonallelic - NAHR), which can result in deletion, duplication or inversion of a gene or more genes. Balanced inversions can result in a hemizygous polymorphism has been found that the critical region for this inverted SWB (SWBinv-1) with greater frequency among parents of individuals with WBS. Published data suggest that individuals inversion SWBinv-1 has a 22-25% chance of having a child with SWB, compared with the general population (5.8%). We we developed a strategy for screening potential carriers SWBinv-1, among the parents of individuals with WBS, so we can check the frequency of this inversion in both parents of children with SWB as between parents of children without SWB in Brazil. Thus analyzes of interphase nuclei were performed on blood smear by technique hybridization in situ by fluorescence (FISH) analysis and compared to metaphase and interphase lymphocyte culture. Were part of the sample group and 38 couples in the control group 20 couples. Of the 38 couples in the sample group ...

A síndrome de Williams-Beuren (SWB) é uma rara afecção genética, caracterizada por varias anormalidades físicas, incluindo dismorfismos faciais, anomalias cardiovasculares, deficiência intelectual e de crescimento, perfil cognitivo característico e ocasionalmente, hipercalcemia infantil transitória, com prevalência de 1/7500. A etiologia da SWB é uma deleção hemizigótica de genes contíguos na região cromossômica 7q11.23. Os tamanhos das deleções mais comum são de 1,5 e 1,8 Mb e abrangem 28 genes. O mecanismo de deleção esta diretamente ligado a regiões cromossômicas repetitivas, denominadas Low Copy Repeats (LCR). Estas regiões repetitivas estão distribuídas por todo genoma, constituindo cerca de 5% de seu total e são o substrato para as recombinações cromossômicas (crossing-over) durante o processo meiótico. Em algumas ocasiões o processo de recombinação pode ocorrer de maneira desigual entre homólogos não alélicos (nonallelic homologous recombination – NAHR), o que pode resultar na deleção, duplicação ou inversão de um gene ou mais genes. Inversões balanceadas podem acarretar em um polimorfismo hemizigótico, tendo sido verificado que a região critica para SWB esta invertida (SWBinv-1) com maior frequência entre genitores de indivíduos com SWB. Dados da literatura sugerem que indivíduos portadores da inversão SWBinv-1 tem uma probabilidade de 22-25% de terem um filho com SWB, comparado com a população geral (5,8%). Nós desenvolvi mos uma estratégia para triagem de possíveis portadores de SWBinv-1, dentre os genitores de indivíduos com SWB, para podermos verificar a frequência desta inversão tanto em pais de crianças com SWB como entre pais de crianças sem SWB no Brasil. Desta forma foram realizadas analises de núcleos interfásicos em esfregaço de sangue pela técnica de hibridação”in situ” por fluorescência (FISH) e comparamos com ...
Keywords: Williams, Síndrome de; Pais e filhos; Citogenetica humana; Hibridização in situ; Aconselhamento genetico; Genetic counseling; Williams syndrome